Understanding the relationship between urban outdoor temperatures and indoor air-conditioning energy demand in Zimbabwe. (October 2017) - Mushore, Terence Darlington; Odindi, John; Dube, Timothy; Mutanga, Onisimo
Highlights: Urbanization induced thermal elevation increases household energy consumption through air conditioning. Landsat and in-situ temperature data useful to long-term determine trends in air conditioning energy requirements. Energy consumption in residential of areas Harare increased with maximum temperature in hot season. Based on degree days, temperature rise due to surface alteration may increase air-conditioning energy consumption in Harare. Low-income urban strata vulnerable to extreme heat as they do not afford air-conditioning. Abstract: Urbanization causes thermal elevation which increase household energy consumption through air conditioning to reduce human heat stress. The objective of this study was thus to quantify the long term changes in potential energy requirements for indoor space warming and cooling in the built environment of Harare using remotely sensed satellite data. Landsat and in-situ temperature data were used to determine land use and land cover distribution, as well as to estimate trends in air conditioning energy requirements between 1984 and 2015. Daytime Heating Degree Days (HDD) and the Cooling Degree Days (CDD) derived from Landsat thermal data and in situ temperature measurements were used as a measure of indoor heating and cooling energy in the cool and hot season, respectively. Due to surface alterations from urban growth between 1984 and 2015, surface temperature increased on average by 2.26 °C and by 4.10 °C in the cool and hot season, respectively. This decreased potential indoor heating energy needed in the cool season by 1 ° day and increased indoor cooling energy during the hot season by 3 ° days. In-situ observations revealed that energy consumption in residential areas Harare increases with temperature in summer and the opposite in winter. Findings in this are important for implementation of mechanisms to rationalize power supply based on spatial differences in levels of need for air conditioning. The findings are also relevant for authorities to devise measures to capacitate the most vulnerable societies, such as by subsidizing electricity for the urban poor, and ensure that they are protected from stress due to low or high temperature.